Forecasting Technology for Planning Decisions - Jones, Harry; Twiss, Brian C. (London: Macmillan, 1978)
This book is concerned with systematic forecasting for technological decision making in the furtherance of business or government objectives.
"A Petrocelli book."
Includes bibliographies and index.
ne 26/03/2018
Loan
Keywords: Technological Forecasting